The role of land bridges, ancient environments, and migrations in the assembly of the North American flora. Issue 5 (5th March 2018) - Graham, Alan
Abstract: Continental‐scale assembly of floras results from past and present in situ diversification in association with several external processes. Among these processes are the making and breaking of connections among landmasses. Connections among landmasses are constantly in flux as are the climates and landscapes along the connection corridors, so that these corridors, or land bridges, may either facilitate or restrict migration at a given time. Across land bridges, changing landscape‐level and organismal factors include the dispersal potential and vectors of propagules, competition, predation, and distributions altered by pathogens. Assembly of a flora is, therefore, the outcome of complex, interacting, temporally‐varying factors that render simplistic explanations unlikely. In the case of North America, the continent experienced ephemeral connections with adjacent regions via five land bridges over the last 100 Ma at different times and under different climates and specific landscape morphologies, including edaphic characteristics. Here, I emphasize the earliest of these connections, Beringia, which probably comprised an initially‐incomplete land bridge during the Cretaceous and Paleocene resulting from compression, fragmentation, and rotation of Asian‐North American sub‐blocks as North America began moving westward from the northern portion of the Mid‐Atlantic Ridge. During the same time, additional land was added to Beringia with accretion of terranes and the subduction of the northern edge of the Pacific Plate beneath the North American‐Asian Plates in the Eocene to form the Aleutian Islands. Other connections between North America and adjacent landmasses were the North Atlantic, the Antilles, Central America, and the Magellan land bridge.